Avaliação de carvões vegetais, carvões vegetais ativados, casca de arroz e fosfogesso como materiais absorvedores em processos de aquecimento por micro-ondas - Oliveira, Gabriela Gil de (2021)
Microwave heating has advantages such as speed, selectivity and simple operational control. However, for an effective heating, an appropriate interaction between the material of interest and the microwave is necessary. This is due to the fact that there are different forms of electromagnetic waves acting on materials, which can be reflected, absorbed or not suffer any attenuation when it contacts the matter. In view of this, there is a demand for research and use of the so-called absorber materials, which are able to absorb microwave energy and dissipate it in the form of heat. The present work aimed to evaluate how activated and non-activated carbon, rice husk and phosphogypsum, affect the efficiency of microwave heating process and investigate their behavior as absorbent materials. The charcoals are derived from Eucalyptus urograndis wood, endocarp from the fruit of macauba and lignin. Heating tests were performed by mixing each material with sand, which is a material transparent to microwave radiation. A 3k Factorial Design of Experiments (DOE) was performed, in which the studied factors were the microwave power and the mass concentration of materials in a mixture with sand. The dependent variable analyzed was the heating rate. Both factors had a significant and positive influence on the heating rate of non-activated and activated carbon and rice husk. For phosphogypsum, the heating rate was affected only by the microwave power. Besides that, carbon activation process increased the absorption and heating potential, due to the greater surface area generated by the process. The highest values of heating rate were obtained in the tests carried out with eucalyptus wood activated carbon. Dielectric properties were measured by coaxial probe method, obtaining characteristic values of absorbent materials for non-activated and activated carbons and for rice husk. Results achieved for phosphogypsum indicate inability of microwave absorption.